Nanocrystal‐Enabled Front‐Surface Bandgap Gradient for the Reduction of Surface Recombination in Inverted Perovskite Solar Cells. Issue 10 (8th August 2021) - Xu, Zhiwei; Guo, Mingxuan; Bo, Jun; Chen, Xingtong; Wan, Peng; Chen, Mengyu; Li, Qinyi; Luo, Chengzhao; Chen, Yu; Chen, Song
Abstract : A bandgap gradient at the front surface of solar absorbers can effectively suppress surface recombination while not affecting photocurrent. Herein, it is demonstrated that a front‐surface gradient can be formed in an inverted perovskite cell by introducing perovskite quantum dots (QDs) between the hole‐transporting layer (HTL) and the remaining absorber. Ultraviolet photoelectron spectroscopy reveals that, with the addition of CsPbBr3 QDs onto the HTL substrate, the subsequently deposited MAPbI3 is converted from mild p‐type to n‐type, and the resultant band alignment can effectively reduce the electron concentration at the front surface without significantly affecting hole extraction. Multiple independent characterizations further confirm the reduction of surface recombination. As a result, the inverted MAPbI3 cells exhibit an open‐circuit voltage of 1.154 V, which translates to a nonradiative recombination loss of 0.15 V and a power conversion efficiency of 20.51%. Abstract : Even without defect passivation, the surface recombination of perovskite solar cells can be suppressed by reducing the concentration of minority carriers at the front surface. By introducing a wide‐gap perovskite, CsPbBr3 nanocrystals, to the front surface, the inverted MAPbI3 cells can achieve significant enhancement of open‐circuit voltages without losing photocurrent.